The end of the end of good work? : work organisation or lean production in the Volvo organisation - Wallace, Terry (International journal of operations & production management ;, 2004)
In recent years, assembly lines have been reintroduced in the Swedish automotive industry and, in many cases, have replaced those so-called alternative assembly systems which had their roots in the 1970s. This paper reviews and evaluates some explicit reasons given for the return to the assembly line. It also considers whether the decisions to replace alternative assembly systems with assembly lines may have been driven by other factors and mechanisms than those implicit in these arguments and, if so, what other factors could explain their reintroduction. There is also a discussion of which di.